Analisis daya sang kompetitif komoditas kopi (Coffea sp.) Indonesia di negara tujuan ekspor - Suhaeni; Sabrina Tasya (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Coffee is one of Indonesia’s main export commodities, reaching five continents: Africa, America, Asia, Australia, and Europe. In 2020, Indonesia was the fifth-largest coffee-exporting country in the world, with a transaction value of US$809.164 million. However, this figure declined by 7.24% compared to 2019. This study aims to analyze the competitive advantage of Indonesian coffee in export destination countries in 2020 and to identify the most potential markets for Indonesian coffee products. A quantitative descriptive approach was used in this research. The Export Product Dynamics (EPD) method was applied to assess the level of competitiveness by analyzing the market position of Indonesian coffee in various destination countries. The results indicate that Germany is the most promising export destination for Indonesian coffee, as it falls into the "Rising Star" quadrant—indicating strong competitiveness and positive trade dynamics.